The Application of Internet Multimedia Technology in the Preschool Education Music Courses - Zhilin Liu, Bowang Chen, Dan Cheng (Forest Chemicals Review, 2022)
With the development and popularization of multimedia technology and the improvement of definition quality, this multimedia instructing method has been widely used in the training of music and other classrooms. The perfect combination of computer and music also brings a kind of fresh air to classroom music training workers. The interaction and coordination of the two makes this multimedia form play an important role in music training in the classroom. In the current music training, multimedia training technology has not only become an advanced method and training tool for comprehensively promoting the development of quality definition, but also provides us with a function with its rich expressive power, strong inclusive beauty and good mutual control. This article explores the application of multimedia video courseware production methods under the Internet in the training of music courses, and elaborates on the training characteristics of music courses in some relevant literature data, and then its foundation the paper puts forward the advantages of Internet multimedia courseware in music training, paving the way for the following investigations, through questionnaires to investigate the current use of multimedia courseware in music classrooms and what impact it has brought to students, the survey results show that the use of multimedia courseware in music classes is still relatively frequent at this stage. More than 40% of teachers use frequently, and more than 34% use general ones. This shows that multimedia courseware has become a training aid for music classroom training. And with the promotion of multimedia technology, the multimedia construction of the school is basically complete at this stage.